Tinjauan Komprehensif Peran Ketua PKK Dalam Membangun Masyarakat Melalui Pendidikan dan Literasi - Sumiati Sumiati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Abstract The role of the PKK Chair in advancing society, especially through the fields of education and literacy, has significance that cannot be underestimated. Her position as PAUD Mother, Literacy Mother, and DWP advisor, Chair of the PKK has a great influence in community development efforts. This article aims to provide a comprehensive overview of how the role of the PKK Chair influences community development through education and literacy. Various aspects discussed include: Educational Advocacy, Organizing Educational Programs, Empowering Teachers and Education Personnel, and promoting literacy. Through his active role and involvement in these various initiatives, the PKK Chair can make a significant contribution to improving the quality of life and potential of society as a whole.